Improving Islamic Education Learning Outcomes with Problem Based Learning Models and Discussion Methods - Donal (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using problem based learning models and discussion methods. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics. The results of the study indicate that problem based learning models and discussion methods can improve student learning outcomes in Islamic religious education learning. Thus, the use of problem based learning models and discussion methods can be used as an alternative to improve student learning outcomes in Islamic religious education learning.